2019
DOI: 10.1007/s10661-019-7567-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hungarian monitoring results and source localization of the 106Ru release in the fall of 2017

Abstract: Anthropogenic 106 Ru has been detected in the environment from late September to early October 2017 by several European environmental radiological monitoring networks. The paper presents the comprehensive evaluation of Hungarian monitoring results related to the occurrence of 106 Ru in various environmental compartments (airborne particulates, deposition, plants, and terrestrial indicators), which was implemented to determine the temporal and spatial variation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…More recently, Hopp et al reported measurements of stable Ru in an environmental filter paper sample where 106 Ru was detected. The filter paper collection was part of a larger event where 106 Ru was detected across Europe during several months in the fall of 2017. , The stable Ru isotopic composition in the paper was consistent with release from spent fuel and comparison with select values reported for different reactor types pointed toward a water–water energetic reactor (VVER) as the source of the emissions . This prior work suggested that 106 Ru measurements could have important future applications in environmental monitoring, as this volatile radioisotope (RuO 4 , boiling point: 40 °C) can be released in nuclear accidents and other nuclear activities. , …”
Section: Introductionmentioning
confidence: 91%
“…More recently, Hopp et al reported measurements of stable Ru in an environmental filter paper sample where 106 Ru was detected. The filter paper collection was part of a larger event where 106 Ru was detected across Europe during several months in the fall of 2017. , The stable Ru isotopic composition in the paper was consistent with release from spent fuel and comparison with select values reported for different reactor types pointed toward a water–water energetic reactor (VVER) as the source of the emissions . This prior work suggested that 106 Ru measurements could have important future applications in environmental monitoring, as this volatile radioisotope (RuO 4 , boiling point: 40 °C) can be released in nuclear accidents and other nuclear activities. , …”
Section: Introductionmentioning
confidence: 91%